2018
DOI: 10.3390/catal8070261
|View full text |Cite
|
Sign up to set email alerts
|

Fast Pyrolysis of Sunflower Oil in the Presence of Microporous and Mesoporous Materials for Production of Bio-Oil

Abstract: Abstract:The present work describes the study of micro (H-ZSM-5) and mesoporous structures, aiming at their application in the production of renewable fuels through the thermos-catalytic pyrolysis process both were synthesized hydrothermally and characterized by X-ray diffraction, thermal analysis, infrared spectroscopy, nitrogen adsorption, and surface acidity. The catalytic effect of the materials mentioned, as well as their mechanical mixtures in the proportions of H-ZSM-5 (75% wt) and AL-MCM-41 (25% wt); … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Considering the advantages of H-ZSM-5 and Al-MCM-41, researchers have altered the shape selectivity and porosity of catalysts to allow multi-step/cascade reactions to take place [21][22][23][24] in order to render a proper design of catalytic pyrolysis process of biomass and to provide high activity, selectivity, and longer life catalyst. Araujo et al [25] investigated the catalytic effect of mechanical mixtures of H-ZSM-5 and Al-MCM-41 on the quality of bio-oil from sunflower oil. They found that the mixture of 50% H-ZSM-5 and 50% Al-MCM-41 resulted in a balance carbon fraction between gasoline (C 5 -C 10 ), kerosene (C 11 -C 15 ), and diesel (C 16 -C 24 ) ranges, corresponding to 44.7%, 42.2%, and 10.5%, respectively [25].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering the advantages of H-ZSM-5 and Al-MCM-41, researchers have altered the shape selectivity and porosity of catalysts to allow multi-step/cascade reactions to take place [21][22][23][24] in order to render a proper design of catalytic pyrolysis process of biomass and to provide high activity, selectivity, and longer life catalyst. Araujo et al [25] investigated the catalytic effect of mechanical mixtures of H-ZSM-5 and Al-MCM-41 on the quality of bio-oil from sunflower oil. They found that the mixture of 50% H-ZSM-5 and 50% Al-MCM-41 resulted in a balance carbon fraction between gasoline (C 5 -C 10 ), kerosene (C 11 -C 15 ), and diesel (C 16 -C 24 ) ranges, corresponding to 44.7%, 42.2%, and 10.5%, respectively [25].…”
Section: Introductionmentioning
confidence: 99%
“…Araujo et al [25] investigated the catalytic effect of mechanical mixtures of H-ZSM-5 and Al-MCM-41 on the quality of bio-oil from sunflower oil. They found that the mixture of 50% H-ZSM-5 and 50% Al-MCM-41 resulted in a balance carbon fraction between gasoline (C 5 -C 10 ), kerosene (C 11 -C 15 ), and diesel (C 16 -C 24 ) ranges, corresponding to 44.7%, 42.2%, and 10.5%, respectively [25]. More recently, Li et al [9] studied the online upgrading of vacuum pyrolysis of rape straw in a two-stage reactor using H-ZSM-5 and MCM-41.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This Py-GC/MS methodology was reported by Araújo and collaborators. 27 For thermocatalytic pyrolysis, 10% by mass of the catalyst was added to the palm oil and mixed physically until homogenization. Furthermore, through this analysis, the percentage in terms of the peak area (% peak area) of each constituent was calculated.…”
Section: Methodsmentioning
confidence: 99%
“…Dry distillation is an attractive conversion method, where OS is converted into different phases, including shale oil, semi-coke, and gas. Many influencing factors, including shale particle size, pyrolysis atmosphere, pyrolysis temperature, heating rate, and residence time, have been studied to improve the production of shale oil and its quality [6,7].…”
Section: Introductionmentioning
confidence: 99%